Elite avenues: Flyovers, freeways and the politics of urban mobility. Issue 4 (4th July 2018) - Graham, Stephen
Abstract : Development and planning elites across many of the burgeoning megacities of the Global South still work powerfully to fetishise elevated highways or flyovers as part of their efforts at 'worlding' their cities. In such a context, and given the neglect of such processes in recent urban and mobilities literatures, this paper presents an international and interdisciplinary analysis of the urban and vertical politics of raised flyovers, freeways and expressways. It argues that such highways need to be seen as important elements within broader processes of three-dimensional social segregation and secession within and between cities which privilege the mobilities of the privileged. The paper falls into six sections. Following the introduction, the complex genealogies of flyover urban design are discussed. Discussion then moves to the vertical politics of flyovers in the West Bank and post-Apartheid South Africa; the elite imaginings surrounding flyover construction in Mumbai; the political struggles surrounding the ribbons of space beneath flyover systems; and the efforts to bury or reappropriate the landscapes of raised flyovers.